Pengabdian Kepada Masyarakat Sosialisasi Dampak LGBT dan Problematikanya di SMP Al-Hikmah Assalafiyyah - Hafizhah, Salwa; Nabila, Salsa; Nurjanah, Syifa; Bariah, Oyoh (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2025)
The phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) has become an issue affecting the moral and social values of the younger generation, including junior high school students. In addressing the challenges of globalization and the influence of foreign cultures, the